The Relationship between Academic Procrastination and Academic Performance of Freshmen Students from a Teacher Education Institution - Asio, John Mark R. (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
The academic environment is full of challenges and obstacles. With this idea, students promote some unconventional practices in studying. One of which is academic procrastination. This study analyzed the relationship between academic procrastination and academic performance of freshmen students from a teacher education institution. The researcher used a descriptive-correlational research design for this study. Ninety (90) freshmen students took part in the survey using a convenience sampling technique in the academic year of 2018-2019. This study used an adapted instrument for data gathering through a survey. The study also utilized SPSS 20 to analyze the data. Results showed that the respondents procrastinate in their academic activities. In terms of academic performance, professional education subjects got the lowest rating score and the major subjects got the highest. In addition, the program, scholarship status, and religion of the respondents got significant statistical differences. Furthermore, the study also obtained a low indirect relationship between academic procrastination, general education subjects, and professional education subjects. From the findings of the study, the researcher provided pertinent recommendations for parents, students, instructors, and the institution.